Late Onset of Cerebellar Abiotrophy in a Boxer Dog - Sanjeev Gumber; Doo-Youn Cho; Timothy W. Morgan (Veterinary Medicine International)
Cerebellar abiotrophy is a degenerative disorder of the central nervous system and has been reported in humans and animals. This case report documents clinical, histopathological, and immunohistochemical findings of cerebellar abiotrophy in an adult Boxer dog. A 3.5-year-old, female, tan Boxer dog presented with a six-week history of left-sided head tilt. Neurological examination and additional diagnostics during her three subsequent visits over 4.5 months revealed worsening of neurological signs including marked head pressing, severe proprioceptive deficits in all the four limbs, loss of menace response and palpebral reflex in the left eye, and a gradual seizure lasting one hour at her last visit. Based on the immunohistochemical staining for glial fibrillary acidic protein and histopathological examination of cerebellum, cerebellar cortical abiotrophy was diagnosed. This is the first reported case of cerebellar abiotrophy in a Boxer dog to our knowledge.